Responses to anti-adblock filters: theoretical foundations, influential factors, and managerial implications - Redondo, Ignacio; Aznar, Gloria (Journal of Business Economics and Management, 2021)
Ad-supported websites face an increasing loss of monetizable ad impressions due to the rapid spread of adblockers, which allow users to get desired website content without unwanted advertising. As a countermeasure, many of these websites use anti-adblock filters, which detect adblock users and prevent their access to website content unless their adblockers are disabled. Users may certainly respond by disabling their adblockers but also by leaving the website or trying to bypass the anti-adblock filter. To better understand the choice among these responses, we propose a conceptual framework that combines psychological reactance theory along with uses and gratifications theory. We also hypothesize the influence of four user-related factors: (a) more positive (negative) attitudes toward online advertising encourage adblocker deactivation (website abandonment); (b) longer adblock usage experiences enable filter bypassing; (c) wider (narrower) scopes of online activities stimulate filter bypassing (website abandonment); and (d) greater online privacy concerns discourage adblocker deactivation. These hypotheses were supported by a survey conducted by the Spanish advertising industry, but the influence of breadth of online activities was negligible in practice. Our findings suggest the importance of improving attitudes toward online advertising, reducing online privacy concerns, and searching for alternative ways to monetize website visits. First published online 29 October 2020